Active development of social networks and relationships to Chinese small and micro business owners' success - Zhao, Xiangyang; Justus Liebig University Giessen (My University, 2005)
Network-based approach is especially useful for the understanding of the entrepreneurship in those collectivistic cultures like China. Many scholars have pointed out the importance of guanxi (personal connections) in Chinese business practice. However, three major questions have still not been adequately addressed in literature. The first one is the regional differences and similarities on Chinese entrepreneurship and her business owners between urban China and rural China. The second one is the link between different types of guanxi and business success. The third one is how business owners actively establish their social networks in order to achieve high business success. Four studies were conducted in this dissertation to address the above questions. All four studies were tested on two samples of Chinese small and micro business owners. 133 were from Beijing and 78 were from an inland, less developed rural region named Xunyi. Study 1 (Chapter 2) empirically compared the differences and similarities of the entrepreneurship and their business owners between rural China and urban China, taking specifically into account both economic and sociological variables as well as psychological variables. It showed many expected differences in entrepreneurship between urban China and rural China, but showed many unexpected differences and amazing similarities throughout China as well. Study 2 (Chapter 3) conceptualized guanxi into different types and tested the functional value of different types of guanxi in predicting business success. Largely in contrast to the commonly held belief on the importance of guanxi in Chinese business practice, this study only confirmed that guanxi network (especially the guanxi with government officials) was related to business success in less developed rural regions, but not in developed urban areas. Further, by exploring the role of resources exchanged in social networks, this study has gone beyond the sole discussion of the link between guanxi and success to delve into the mechanism behind it. Study 3 (Chapter 4) mainly differentiated three concepts in theory: social skills, social strategies and active and elaborate social strategies. Confirmatory Factor Analyses were employed to reexamine the psychometric traits of the 3-factor social skills scales developed by Baron and Markman (2003) and to test the newly developed active and elaborate social strategies scales. The results showed only part of the social skills scales developed by Baron and Markman (2003) could be clearly reproduced and combined into a second-order factor of social skills. However, the newly developed active and elaborate social strategies scales showed good psychometric traits and also could be combined into a second-order factor of active and elaborate social strategies. Study 4 (Chapter 5) tested a model of active network building and business success. I argued that three psychological constructs are particularly useful for network building: social skills, active and elaborate social strategies and relationship-oriented personal initiative. These three psychological variables can influence business success directly or via social networks (as a mediator). The results showed that government guanxi network is a more consistent and pronounced mediator between three psychological variables and business success, especially in rural, less developed regions, but business guanxi network is not. In general, the two-sample design employed in this dissertation makes me to validate the findings in different contexts, especially to deal with the great divides between urban China and rural China. Based on a relatively large sample size, this study pushes the inquiry on the link between guanxi and business success one step further. The active social approaches developed in this dissertation also enrich the literature on the active approaches in work and organizational psychology and entrepreneurship. Finally, as one of the studies that looks at how guanxi is built and maintained, if these results can be replicated and if they can be shown to be longitudinally valid, they can be used to train people in how to increase their networks and to increase their successes.
Keywords: soziales Netzwerk; Unternehmer; China; Guanxi; soziale Strategie; social network; entrepreneurship; China; Guanxi; social strategy; ddc:150